Liberia : Inclusive Growth Diagnostics - World Bank (Washington, DC, 2013)
Liberia aims to achieve middle-income status by 2030 through broad participation and inclusive growth. The Government's growth strategy aims to accelerate growth through the exploitation of natural resources, while maintaining sound macroeconomic policies, improving the business environment, and prudently allocating aid and commodity-based financing resources to expand infrastructure and formal sector employment. However, Liberia's experience with rapid growth in the 1960s and 1970s, that benefit a small percentage of the population, followed by economic collapse, widespread poverty and social unrest, and civil war, has made policymakers acutely aware that the quality of the growth process is at least as important as the rate of growth. Now that peace has been established and growth is once again on an upward trend, with the reactivation of the iron ore and agriculture sectors, and prospects for oil, promising opportunities for significant growth in the medium to long term, the Government wants to ensure that Liberia's growth over the next two decades will be sustainable and equitable. A key objective of the growth strategy is to avoid the traps posed by dependence on primary resources while creating the basis for economic diversification and employment generation, and providing opportunities and training so that individuals across the country can partake in the growth process. This diagnostic aims to support that strategy by identifying the factors in Liberia's economy that act as binding constraints to inclusive growth.